MENINGKATKAN PENGETAHUAN ISLAM ANAK USIA DINI DI KAMPUNG KALURAHAN, DESA CIBATOK II, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Siti Yansi Apriyanti (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
Early age is a golden age for children, because at this age children have extraordinary physical and mental growth and development. This period is also a period of character formation, personality and character. Early age is also the most important period for children, because it is the main personality formation period. Therefore it is important to be given religious education from an early age. The importance of inculcating religious values ​​from an early age in order to create human beings with noble character. Islamic education is given to children from an early age through prior introductions to the creation of Allah Subhanahu wa Ta'ala about nature and everything in it. Then introduced worship, especially prayer, ablution, reading daily prayers. Also taught are habits with Islamic nuances in order to form good morals. The program we run is in the form of teaching at Kampung Kalurahan, Cibatok II Village, Cibungbulang District, Bogor Regency, and teaching at the Al Hikmah Early Childhood Education Center. In the religious sector, activities are carried out routinely almost every day, namely teaching the Qur'an Education Park and also reciting youth lessons. In the economic field, activities are carried out, namely counseling on saving from an early age. The methods used are guidance and counseling methods, learning methods through playing, talking stick learning methods, learning methods with media.